Synthesis of P-chiral phosphine compounds by palladium-catalyzed C–P coupling reactions. Issue 79 (10th September 2020) - Wang, Cuiying; Yue, Chang-Duo; Yuan, Jia; Zheng, Jia-Lian; Zhang, Ying; Yu, Hong; Chen, Jian; Meng, Sixuan; Yu, Yang; Yu, Guang-Ao; Che, Chi-Ming
Abstract : An efficient C–P coupling reactions of enantiopure tert -butylmethylphosphine-boranes with aryl and heteroaryl halides is developed by using Pd(OAc)2 /dppf as a catalyst, affording a series of P-chiral phosphines (up to 99% ee). Abstract : An efficient C–P coupling reaction of enantiopure tert -butylmethylphosphine-boranes with aryl and heteroaryl halides is developed by using Pd(OAc)2 /dppf as a catalyst, affording a series of ( S ) or ( R )- P -chiral phosphines in moderate to high yields and with ee values up to 99% ee. Moreover, the reaction time could be reduced from 72 h to 6 h with increased ee values under microwave irradiation.